Co- and postseismic subaquatic evidence for prehistoric fault activity near Coyhaique, Aysén Region, Chile - Vervoort, Morgan; Wils, Katleen; Vanneste, Kris; Urrutia, Roberto; Pino, Mario; Kissel, Catherine; De Batist, Marc; Van Daele, Maarten (Natural hazards and earth system sciences, 2024)
Chilean Patagonia is confronted with several geohazards due to its tectonic setting, i.e., the presence of a subduction zone and numerous fault zones, e.g., the Liquiñe-Ofqui Fault Zone (LOFZ). This region has therefore been the subject of numerous paleoseismological studies. However, this study reveals that the seismic hazard is not limited to these large tectonic structures by identifying past fault activity near Coyhaique in Aysén Region. Mass-wasting deposits in Lago Pollux, a lake located ca. 15 km SW of this region's capital, were identified through analysis of reflection-seismic data and were linked to a simultaneous event recorded in nearby Lago Castor. Furthermore, a coeval ∼50-year-long catchment response was identified in Aysén Fjord based on the multiproxy analysis of a portion of a sediment core. Assuming that this widely recognized event was triggered by an earthquake, ground-motion modeling was applied to derive the most likely magnitude and source fault. The model showed that an earthquake rupture along a local fault, in the vicinity of Lago Pollux and Lago Castor, with a magnitude of 5.6–6.8, is the most likely scenario.